Quality of life improves following laparoscopic hemifundoplication in neurologically non-impaired children with gastroesophageal reflux disease: a propensity score-matched analysis - Frongia, Giovanni; Weitz, Daniel; Bauer, Jan; Probst, Pascal; Steffens, Franziska; Pfisterer, Dennis; Mehrabi, Arianeb; Günther, Patrick (Journal of investigative surgery, 2022)
Quality of life (QOL) data following pediatric fundoplication for gastroesophageal reflux disease (GERD) are rare. Present study assessed the QOL in neurologically non-impaired children before and after laparoscopic hemifundoplication (LHF) in comparison to healthy controls. PedsQL™ questionnaires assessed data on gastrointestinal symptoms (GIS) and general well-being (GWB) were compared in a propensity score-matched analysis (60 patients’ pairs for time-point of surgery and 51 for follow-up). Preoperatively, the LHF group had more GIS (72.2 ± 53.9 vs. 38.8 ± 31.6; p < 0.001) and a lower GWB (16.7 ± 5.5 vs. 23.8 ± 3.5, p < 0.001) compared with controls. Postoperatively, GIS decreased significantly (74.3 ± 52.9 vs. 36.3 ± 33.5; p < 0.001) and the GWB was significantly higher (16.2 ± 6.0 vs. 20.8 ± 5.8; p < 0.001). GIS were similar in the LHF and control groups (39.1 ± 36.4 vs. 40.1 ± 31.0; p = 0.885) but GWB was lower in the LHF group than the control group (20.5 ± 6.3 vs. 23.4 ± 3.9; p = 0.009). QOL significantly improves after LHF in neurologically non-impaired children.
Online veröffentlicht: 29. November 2020
Gesehen am 17.04.2024